Gestão de risco na segurança do paciente com transtorno mental - Vantil, Fernanda Cordeiro Sirtoli (2017)
Introduction: Risk management is an integral part of all organizational processes, and occurs simultaneously with the institution's activities. When referring to health care, Patient Safety is an essential axis of quality of service, but the discussion of this issue is still limited in the area of mental health. General objective: To implement risk management in patient safety at a reference hospital in mental health. Specific objectives: Identify risk factors that influence the safety of patients with mental disorders; develop patient safety protocols; construct the risk management diagram and monitored events in the safety of patients with mental disorders; to develop a textual proposal for software for internal management of incident reports. Methodology: It was used the action research, of qualitative approach. Participants were the 13 members of the multidisciplinary team responsible for assisting patients with mental disorders. Data collection took place from October 3, 2016 to March 27, 2017. The 13 participants were divided into two groups. Each group participated in 8 meetings, in addition to the closing meeting that was held in a single event with all participants. Results: From the analysis of the textual corpus of the meetings, we obtained 03 categories: Construction of the protocols; Diagram and textual design of software for internal management of incident reports and action research as a collective strategy for the organization of risk management in the safety of patients with mental disorders. Product: Three products were developed: tree diagram of risk management in the safety of patients with mental disorders; Patient Safety Protocols with Mental Disorder, management technology consisting of seven protocols; textual proposal of software for internal management of incident notifications. Conclusion: The management tools were elaborated with the effective and integral participation of all the multidisciplinary team. In addition to achieving the objectives, it is noteworthy that some changes occurred in the institution of the study. The most notable was the creation and official appointment of the Patient Safety Center and the invitation to the researcher to assume the presidency of this service. In this way, it is estimated that the research started a process of institutional culture change regarding Patient Safety. For nursing care in mental health, the results of this study provide a baseline for care to be offered with quality, assuring to the professional a standardization of actions based on the principles of patient safety. Finally, this study reaffirms the need for a scientific discussion about mental health and safe care, the involvement of all the team in the development of practices and the effective management of risks to the safety of patients with mental disorders.